Itikad Baik Dalam Pendaftaran Merek: Studi Perlindungan Hukum Pemilik Merek Terkenal Di Indonesia - Medisita Nurfauziah Istiqmalia; Iwan Erar Joesoef (Jurnal Penegakan Hukum Indonesia, 2021)
One of the disputed cases of the ALSTYLE Mark filed by Gildan Active-wear which proved its brand fame filed a legal action against the same trademark owner as the Darmanto trademark owner. The Commercial Court and Supreme Court of the Republic of Indonesia have given different considerations to the protection of marks in the settlement of Mark disputes. The formulation of this problem is how well-known trademarks are protected in Indonesia in the event that similar marks have been registered and how the judges of the Commercial Court consider legal protection for well-known marks. This research method uses normative juridical legal research methods with analysis techniques using qualitative data. The result of this research is the legal protection of the right holder of a well-known trademark in the event that there is a trademark that has been registered at the Directorate of IPR, then based on the legalprovisions of the Directorate of IPR trademarks can cancel a brand that has the same in essence and in its entirety to a well-known mark for similar goods. The criteria for a well-known brand can be seen from the general knowledge of the public and the reputation of the brand which is obtained due to intense promotion and investment. Second, the legal consideration of the Panel of Judges states that even though trademark registration follows a first to file system it does not mean neglecting the good faithof a well-known brand and overriding the status of a well-known trademark belonging to Gildan Activewear SRL.